2010
DOI: 10.1017/s0022149x10000301
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and spatial distribution of monogeneans on the gills ofOreochromis mossambicus(Peters, 1852) from two lakes of the Limpopo River System, South Africa

Abstract: An investigation was conducted into the parasitic infection of an indigenous cichlid, Oreochromis mossambicus, collected seasonally from the Nwanedi-Luphephe dams of the Limpopo River System from July 2007 to April 2009. Of 157 host specimens examined, 115 (73.25%) were infected by at least one gill parasite. In all, 1565 monogenean specimens were collected, belonging to five different species and two genera: Cichlidogyrus (C. halli, C. sclerosus, C. tilapiae and C. dossoui) and Scutogyrus (S. longicornis). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…The present study and previous attempts to find gill parasites in native O. mossambicus populations (Madanire-Moyo et al 2011;Olivier et al 2009;Sara et al 2013) consistently reported the presence of parasites, with species richness ranging from one to six species (median richness: three species). In contrast, no parasite was found in the invasive host population of New Caledonia.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The present study and previous attempts to find gill parasites in native O. mossambicus populations (Madanire-Moyo et al 2011;Olivier et al 2009;Sara et al 2013) consistently reported the presence of parasites, with species richness ranging from one to six species (median richness: three species). In contrast, no parasite was found in the invasive host population of New Caledonia.…”
Section: Discussionmentioning
confidence: 50%
“…Considering the lowest prevalence levels already reported in the native range (i.e., 73.25 %, Madanire-Moyo et al 2011;and 47.10 %, Sara et al 2013) and the sample size in New Caledonia (n = 62), this null estimated parasite prevalence appears unlikely to be due to sampling error in the invasive populations, but rather results from a substantially lower prevalence in the invaded range (binomial test for a prevalence level lower than 47.10 % in the native range: p < 0.0001). Actually, our sampling design still provides statistical support (p = 0.0416) assuming that parasite prevalence in New Caledonia would lie below 5 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…was positive. A similar finding was reported among Cichlidogyrus halli, Cichlidogyrus sclerosus, Scutogyrus longicornis, Cichlidogyrus dossoui and Cichlidogyrus tilapiae, and among S. longicornis, C. dossoui and C. tilapiae in the gills of Oreochromis mossambicus, due to lack of competition among these monogenoidean species (MADANIRE-MOYO et al, 2011). In contrast, the competition between Dactylogyrus carpathicus and Dactylogyrus malleus was due to high abundance and microhabitat preference for the gills of Barbus barbus (KADLEC et al, 2003).…”
Section: Discussionmentioning
confidence: 52%
“…Some authors include intrinsic factors such as the need to increase chances of locating a mate by having a narrow microhabitat niche and environmental conditions. Among the environmental factors, water current has been identified as among the most important factor determining site specificity (Madanire-Moyo et al, 2010;Le Roux et al, 2011) with the suggestion that middle arches offer a hydrodynamically protected site .…”
Section: Discussionmentioning
confidence: 99%